2012
DOI: 10.1111/j.1349-7006.2012.02316.x
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance tumor targeting imaging using gadolinium labeled human telomerase reverse transcriptase antisense probes

Abstract: To develop a molecular probe for MRI detection of human tumor telomerase reverse transcriptase (hTERT) mRNA expression. Uniformly phosphorothioate‐modified hTERT antisense oligonucleotide (ASON) homing hTERT mRNA was labeled with gadolinium (Gd) through the bifunctional chelator 1,4,7, 10‐tetraazacyclododecane‐N, N', N'', N'''‐tetraacetic acid (DOTA) stirred within 45 minutes at 60°C. The Gd labeled probes were characterized in vitro. The cellular uptake rate and biodistribution of 99mTc‐DOTA‐ASON was measured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…Tumors (arrows) all showed different enhancement level at 0.5 h, but in Gd-DOTA-ASON (upper line), the enhancement remained at 6 h, while Gd-DTPA (middle line) decreased obviously from 2 h (repetition time, 561 ms, echo time, 14 ms, and field of view, 4 cm); Gd-DOTA-SON (lower line) showed a similar trend to that of Gd-DOTA-ASON but with lower enhancement (adopted from Ren et al [61]).…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Tumors (arrows) all showed different enhancement level at 0.5 h, but in Gd-DOTA-ASON (upper line), the enhancement remained at 6 h, while Gd-DTPA (middle line) decreased obviously from 2 h (repetition time, 561 ms, echo time, 14 ms, and field of view, 4 cm); Gd-DOTA-SON (lower line) showed a similar trend to that of Gd-DOTA-ASON but with lower enhancement (adopted from Ren et al [61]).…”
Section: Figurementioning
confidence: 99%
“…18 F-FDG is the most widely used imaging agent based on small molecules, which is clinically applied for cancer imaging [ 60 ]. Ren et al [ 61 ] reported the use of gadolinium (Gd) to label uniformly phosphorothioate-modified human tumor telomerase reverse transcriptase (hTERT) antisense oligonucleotide (ASON) targeting hTERT mRNA and conducted a study in BALB/c nude mice with 7.0T Micro-MRI, showing that Gd-DOTA-ASON was a potential intracellular MR contrast probe for detection of telomerase-positive carcinomas ( Figure 6 ).…”
Section: Imaging Agentsmentioning
confidence: 99%
“…In 2012, Ren et al reported the 99m Tc radiolabeling of human tumor telomerase reverse transcriptase hTERT antisense oligonucleotide through a bifunctional chelator DOTA. In this approach, the ASO sequence was conjugated with DOTA-NHS at the 3′-end amine with more than 85% radiochemical purity ( Ren et al, 2012 ).…”
Section: Radiometalsmentioning
confidence: 99%
“…In 2012, Ren et al reported the 99m Tc radiolabeling of hTERT (human tumor telomerase reverse transcriptase) antisense oligonucleotide (ASON) through the bifunctional chelator DOTA. The ASON sequence, 5′-TAG AGA CGT GGC TCT TGA-3′, was conjugated with DOTA–NHS via the amine-functionalization of the oligonucleotides at the 3′-end [51]. DOTA–NHS–ester was prepared using the published procedure [52,53].…”
Section: Radiolabeling Of Ligands For Spect Imagingmentioning
confidence: 99%
“…Then, the semistable amino-reactive intermediate DOTA–NHS–ester was added to ASON and radiolabeled by 99m TcO 4 − with SnCl 2 at room temperature (Figure 7). The reported radiochemical purity was 85% [51]. Calzada et al successfully linked both 99m Tc and 67 Ga to an aptamer (Sgc8) through the HYNIC and DOTA chelators, which showed desirable biodistribution and pharmacokinetic properties [47].…”
Section: Radiolabeling Of Ligands For Spect Imagingmentioning
confidence: 99%